Mechanical response analysis and optimization of snap on Prefabricated Concrete Pavement Slab. Issue 3 (March 2020) - Chunhua, Hu; Xuan, Wang
Abstract: In this paper, a kind of assembled cement concrete pavement slab was numerical analysis to investigate the influence of the size of the tongue and groove joint on load transfer capacity between slabs and the maximum stress in the slab. And the load transfer capacity of the slab and the maximum stress in the panel of different sizes are optimized.